Expressive Speech in the Comment Column on the Instagram Account @infopku - Fitri Matrona Simanullang; Fatmawati (RETORIKA: Jurnal Ilmu Bahasa, 2024)
The aim of this research is to find out and describe the expressive speech used by netizens in the comment’s column of the Instagram account @infopku_. This research uses a qualitative descriptive methodology. The data source in this research is comments on the Instagram post @infopku_ on Wednesday 08 May 2024 regarding "Traditional Market Parking Fees in Pekanbaru Drop to Rp. 1000". The data collection technique is documentation, listening and taking notes. The data analysis used is content analysis. The results of the analysis show that in the Instagram comment column @infopku_ there are a number of expressive utterances consisting of thanking, praising, forgiving, blaming, congratulating, complaining, and hoping. Expressive speech acts of praise dominate more than other expressive speech acts. In this case, netizens praised the mayor's decision to reduce parking rates in traditional market areas, which greatly benefits the community.